2015
DOI: 10.1093/glycob/cwv108
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-type O-glycosylation is controlled by short- and long-range glycopeptide substrate recognition that varies among members of the polypeptide GalNAc transferase family

Abstract: A large family of UDP-GalNAc:polypeptide GalNAc transferases (ppGalNAc-Ts) initiates and defines sites of mucin-type Ser/Thr-O-GalNAc glycosylation. Family members have been classified into peptide- and glycopeptide-preferring subfamilies, although both families possess variable activities against glycopeptide substrates. All but one isoform contains a C-terminal carbohydrate-binding lectin domain whose roles in modulating glycopeptide specificity is just being understood. We have previously shown for several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(154 citation statements)
references
References 62 publications
(138 reference statements)
8
144
1
1
Order By: Relevance
“…In addition, kinetic analysis was performed on several of these purified recombinant products before and after tag removal with TEV protease. The results, exemplified by ST6GALNAC2 (Supplementary Table 4), indicated that the enzymes had comparable activity as GFP fusion proteins or released catalytic domains17,28. As the construct library was being completed, we further characterized several of these expression products and the results effectively identified GT substrate specificities2830, corrected the glycan linkage elaborated by a GT31, resulted in chemoenzymatic synthesis of novel glycan structures32, and supported selective exoenzymatic labeling (SEEL)33 of cell surface glycans, demonstrating the utility of our expression vector library as a tool for various glycoenzyme studies and applications in glycobiology.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, kinetic analysis was performed on several of these purified recombinant products before and after tag removal with TEV protease. The results, exemplified by ST6GALNAC2 (Supplementary Table 4), indicated that the enzymes had comparable activity as GFP fusion proteins or released catalytic domains17,28. As the construct library was being completed, we further characterized several of these expression products and the results effectively identified GT substrate specificities2830, corrected the glycan linkage elaborated by a GT31, resulted in chemoenzymatic synthesis of novel glycan structures32, and supported selective exoenzymatic labeling (SEEL)33 of cell surface glycans, demonstrating the utility of our expression vector library as a tool for various glycoenzyme studies and applications in glycobiology.…”
Section: Discussionmentioning
confidence: 98%
“…The O-glycans are known to express species-and tissue-specific antigens that change during cell differentiation and oncogenesis (2,6), and mediate some of the above-mentioned mucin functions (7). However, the involvements of specific O-glycan structures in many processes are yet to be determined (2), assignments being hampered by the diversity of extensions at the core-monosaccharide, GalNAc, and multiplicity of chain lengths and branching patterns (5,8,9), and often the limited amounts of glycans available. Thus high-throughput and microscale methodologies are needed for deconvolution and functional assignments of individual O-glycans within O-glycomes as cues to large scale syntheses of desired glycan sequences for exploitation (10,11).…”
mentioning
confidence: 99%
“…Inhibition of ppGalNAc-T3 occurred with an IC 50 of 7 µM and was undetectable against ppGalNAc-T2. T3Inh-1 also lacked activity against ppGalNAc-T6 (Figure 2B), which is the isozyme considered most closely related to ppGalNAc-T3 (Bennett et al, 2012Revoredo et al, 2016).
10.7554/eLife.24051.011Figure 2.T3Inh-1 is a direct mixed-mode inhibitor of ppGalNAc-T3.( A ) Comparison of T2 and T3 sensor activation at the indicated concentrations of T3Inh-1 (n = 3 ± SEM).
…”
Section: Resultsmentioning
confidence: 99%